Employee Motivation Influences on Employee Performance Using Employee Engagement and Job Satisfaction as the Mediating Variables in CV Kam Indonesia - Diana Diana; Endang Sulistyaningsih; Wen Shai Hung (Budapest International Research and Critics University, 2022)
Improvements in employee performance are a critical organizational goal in most companies, especially in the department of human resources. This research aimed to investigate the influence of Employee Motivation on Employee Performance using Employee Engagement and Job Satisfaction as the mediating variables. Using Google Forms, a survey questionnaire was distributed to 117 employees from CV KAM Indonesia, a wholesale grocery company. The obtained data were processed using the SmartPLS software. The data analysis method used was structural equation modeling-partial least square (SEM-PLS) to examine the relations between the variables. The results of this study showed that employee motivation has a direct positive influence on employee engagement and job satisfaction, but not employee performance. Employee engagement and job satisfaction have a direct positive influence on employee performance. Additionally, employee engagement and job satisfaction are proven to fully mediate employee motivation's effect on employee performance. This study has attempted to provide statistical results and a managerial discussion to support the improvement program in CV KAM Indonesia.